2021
DOI: 10.3389/fgene.2021.678994
|View full text |Cite
|
Sign up to set email alerts
|

Human MicroRNAs Interacting With SARS-CoV-2 RNA Sequences: Computational Analysis and Experimental Target Validation

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a novel RNA virus affecting humans, causing a form of acute pulmonary respiratory disorder named COVID-19, declared a pandemic by the World Health Organization. MicroRNAs (miRNA) play an emerging and important role in the interplay between viruses and host cells. Although the impact of host miRNAs on SARS-CoV-2 infection has been predicted, experimental data are still missing. This study started by a bioinformatics prediction of cellular miRNAs po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 57 publications
(74 reference statements)
2
35
0
Order By: Relevance
“…SARS-CoV-2 may act as a sponge of these miRNAs, being potentially titrated on the viral genome and resulting in an altered regulation of canonical miRNA targets [55]. An additional computational analysis confirmed that the SARS-CoV-2 genome potentially associates with host hsa-miR-3529-3p, hsa-miR-451b, hsa-miR-499b-3p, and hsa-miR-5688 [56,73].…”
Section: Host Ncrnas In Cvd and Myocardial Injury Upon Sars-cov-2 Infectionmentioning
confidence: 81%
See 2 more Smart Citations
“…SARS-CoV-2 may act as a sponge of these miRNAs, being potentially titrated on the viral genome and resulting in an altered regulation of canonical miRNA targets [55]. An additional computational analysis confirmed that the SARS-CoV-2 genome potentially associates with host hsa-miR-3529-3p, hsa-miR-451b, hsa-miR-499b-3p, and hsa-miR-5688 [56,73].…”
Section: Host Ncrnas In Cvd and Myocardial Injury Upon Sars-cov-2 Infectionmentioning
confidence: 81%
“…The data reported by Moazzam-Jazi and coworkers indicate that several human lncRNAs preferentially interact with the 5 end of SARS-CoV-2 rather than the 3 end [66], reinforcing the possibility to design RNA-based vaccines against the 5 end of the virus. Accordingly, H19, MIAT, FENDRR, and linc01505 show BS against the SARS-CoV-2 leader sequence [53,56,73,127].…”
Section: The 5 Leader Sequence Of Sars-cov-2 As Target For Ncrna-based Therapiesmentioning
confidence: 93%
See 1 more Smart Citation
“…Under this premise, a relevant inquiry buttressed that some human miRNAs, such as miR-219a-2-3p, miR-30c-5p, miR-378d, miR-29a-3p, and miR-15b-5p, can interact with the viral sequences of SARS-CoV-2. Intriguingly, the outcomes of this investigation stated that the complete complementary target sequences of the aforesaid miRNAs are conserved in some of the newly emerged variants of the virus, i.e., South Africa 501Y.V2 and United Kingdom variant B.1.1.7 ( Siniscalchi et al, 2021 ). Therefore, to obtain an effective and safe miRNA-based treatment for COVID-19, further inquiries should assure that the interactions between human miRNAs and SARS-CoV-2’s genome sequences are conserved in almost all the existing variants of the virus.…”
Section: Future Perspectivesmentioning
confidence: 91%
“…Effective therapeutic strategies against the coronavirus disease 2019 (COVID-19) caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) are desperately needed. In a recent issue of Frontiers in Genetics , Chiara Siniscalchi and collaborators [ 5 ] identify some miRNAs targeting SARS-CoV-2 RNA. Specifically, starting with a well-designed bioinformatic analysis that pinpointed eight candidate miRNAs, the authors went on to validate the functional interaction of five miRNAs (namely miR-15b-5p, miR-29a-3p, miR-30c-5p, miR-219a-2-3p, and miR-378d) with viral sequences in a human lung cell line.…”
Section: Tackling Sars-cov-2 Variants Using Specific Mirna Toolsmentioning
confidence: 99%